Examining the determinants of customer loyalty in the fitness industry: the mediating effect of satisfaction - Wijaya, Faris; Dwita, Vidyarini (Universitas Negeri Padang, 2024)
This study aims to analyze the influence of service quality and customer perceived value on customer loyalty, with customer satisfaction as a mediating variable, at the Max Power Gym fitness center in Padang City. The population comprises 187 active members of Max Power Gym in Padang City, with a sample of 153 respondents. Data were collected through online questionnaires and analyzed using SmartPLS software. The findings reveal that: (1) Service Quality has a positive and significant effect on Customer Loyalty; (2) Customer Perceived Value has a positive and significant effect on Customer Loyalty; (3) Service Quality has a positive and significant effect on Customer Satisfaction; (4) Customer Perceived Value has a positive and significant effect on Customer Satisfaction; (5) Customer Satisfaction has a positive and significant effect on Customer Loyalty; (6) Customer Satisfaction mediates the positive and significant effect of Service Quality on Customer Loyalty; and (7) Customer Satisfaction mediates the positive and significant effect of Customer Perceived Value on Customer Loyalty.